Analysis of Early Intervention Systems for War-Related Trauma in the Middle East: (A Programmatic Synthesis) - Nurzahara Sihombing; M. Agung Rahmadi; Naila Al Madina; Zulpiani Br Sipayung; Khaila Salsabila; Helsa Nasution; Luthfiah Mawar; Andine Mei Hanny (Jurnal Ventilator, 2025)
This study critically examines the effectiveness of early intervention programs in addressing war-related trauma in the Middle East by meta-synthesizing forty-seven interventions implemented between 2010 and 2024. The analysis demonstrates that cognitive behavioral therapy (CBT) based interventions achieved a success rate of 78.3 percent with p value less than 0.001 in reducing post-traumatic stress disorder symptoms, with an effect size of d equal to 0.86 indicating substantial therapeutic strength. Group based interventions showed higher effectiveness (83.2 percent) than individual approaches (71.5 percent), and programs involving family support yielded better recovery outcomes (84.7 percent) than those without family involvement (69.3 percent). Regression analysis identified three primary predictors of successful intervention outcomes, namely intervention duration (beta 0.42, p value less than 0.001), therapist cultural competence (beta 0.38, p value less than 0.001), and the integration of social support systems (beta 0.35, p value less than 0.001). These findings expand on prior studies by Ennis et al. (2020) and Mawar et al. (2025), which were limited to evaluating CBT effectiveness, and also reinforce the significance of cultural dimensions and social support systems as critical determinants. In contrast to the meta analysis by Nocon et al. (2017), which reported an effectiveness rate of 65 percent for individual interventions, the present study reveals the superiority of group based approaches in communal Middle Eastern societies. The novelty of this study lies in its comprehensive identification of culturally sensitive determinants of early intervention success and the formulation of an integrative model positioning family support as an essential component in protocols for war-related trauma care.